Remote Offshore Oil and Gas Platform SCADA System Fault Tree Design and Minimal Cut Sets Analysis - Siva Prasad, M.V. V.; Avadhani, P.S. (International Journal of Computer Sciences and Engineering, 2019)
Safety of the remote oil and gas production platform is vital. Supervisory Control and Data Acquisition System (SCADA) system ensures safe operations at remote platform by remote monitoring and control from main process complex. SCADA system at remote platform comprises of remote radio, field router, and remote telemetry unit (RTU). A frame work in designing fault tree for SCADA system at remote offshore oil and gas production platform presented in this research work. It is presented here to analyze the risk to SCADA system as it is available on corporate LAN. Appearing on internet exposed the SCADA system cyber security threats. Analysis of designed fault tree carried out by applying minimal cut sets (MCS) theorem. Fault tree analysis (FTA) is a failure analysis in which an undesired state of a system is analyzed using Boolean logic to combine a series of lower-level events. FTA is an effective technique to support probabilistic risk assessment; it can also be used as a valuable design tool. Minimal Cut Set is a set such that if any basic event is removed from it, the top event will not necessarily occur if all the remaining events in the cut set occur. MCS analysis performed to identify vulnerable faulty sub systems and their components. This analysis guides us to take appropriate action in advance to mitigate the any eventuality. Present analysis contributes directly in safety analysis. It is essential for human safety and preventing oil spill thus, contributing in environment protection.